PENGARUH DOSIS BAHAN ORGANIK DENGAN KEDALAMAN OLAH TANAH TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KORO PEDANG (Canavalia ensiformis L) DI TANAH GRUMUSOL - Viatno, Andi; Sunaryo, Yacobus; Susilaningsih, Sri Endah Prasetyowati (Universitas Sarjanawiyata Tamansiswa, 2018)
This study aimed to determine the effect of dosage of organic matter and soil tilage depth on the growth and yield of jack bean in grumusol soil. This research was carried out in UPTD field of Food andDevelopment Center, Jl. Yogyakarta-wonosari km 33, playen, gading, Gunungkidul district, special province of Yogyakarta. The area is located at an altitude of 200 meters above sea level with daily temperature between 23-32 0C. The research was conducted from February - July 2017. This research was conducted by using 3 x 3 factorial experiment which was arranged in Completely Randomized Block Design (RAKL). The treatment consists of 2 factors, the first factor was the soil tilage depth consisted of 3 levels namely the depth of 0.15, and 30 cm. The second factor plana the application of green manure of gamal consisting of three levels, namely 10,15, and 20 ton ha-1. Each treatment was repeated 3 times. Observations included plant height, number of leaves, number of flowers, dry weight of plants, number of pods per plant, one hundred seeds weight, dry pods per plant, pod length per plant, seed yield per plot, and seed yield Ha-1. Results indicated thanthere was an interaction between the dosage of green manure and thesoil tilage depth on the yield of jack bean Ha-1. The best result was in the treatment combination of green gamal fertilizer with a dose of 30 tons Ha-1 with soil tilage depth of 20 cm. Treatment of soil depth as well as the dosage of green manure gamal has no significant effect on growthon variable dry weight of plantThis study aimed to determine the effect of dosage of organic matter and soil tilage depth on the growth and yield of jack bean in grumusol soil. This research was carried out in UPTD field of Food andDevelopment Center, Jl. Yogyakarta-wonosari km 33, playen, gading, Gunungkidul district, special province of Yogyakarta. The area is located at an altitude of 200 meters above sea level with daily temperature between 23-32 0C. The research was conducted from February - July 2017. This research was conducted by using 3 x 3 factorial experiment which was arranged in Completely Randomized Block Design (RAKL). The treatment consists of 2 factors, the first factor was the soil tilage depth consisted of 3 levels namely the depth of 0.15, and 30 cm. The second factor plana the application of green manure of gamal consisting of three levels, namely 10,15, and 20 ton ha-1. Each treatment was repeated 3 times. Observations included plant height, number of leaves, number of flowers, dry weight of plants, number of pods per plant, one hundred seeds weight, dry pods per plant, pod length per plant, seed yield per plot, and seed yield Ha-1. Results indicated thanthere was an interaction between the dosage of green manure and thesoil tilage depth on the yield of jack bean Ha-1. The best result was in the treatment combination of green gamal fertilizer with a dose of 30 tons Ha-1 with soil tilage depth of 20 cm. Treatment of soil depth as well as the dosage of green manure gamal has no significant effect on growthon variable dry weight of plant.